Upaya Satuan Sabhara Dalam Mencegah Tindak Pidana Pencurian Dengan Pemberatan Melalui Patrolo Roda Dua Di Polres Cimahi - Bagus Agung Wicaksono (Police Studies Review, 2020)
The focus of this research is about the efforts of the Sabhara Unit in Preventing Theft by Weighting Through Two-Wheel Patrol in Cimahi Regional Police Station. The focus of this study is considered important because of the efforts. The problems raised in this thesis research are: (1) The description of the implementation of two-wheeled patrols in preventing criminal acts of theft by weighting at the Cimaho Regional Police Station, (2) There are factors that inhibit two-wheeled patrols so that theft occurs with weighting at the Cimahi Police Station (3) Efforts made by the Sabhara unit through a two-wheeled patrol in preventing theft by weighting. This study aims to analyze the Sabhara Unit's Efforts to Prevent Theft by Weighting Through Two-Wheel Patrol in Cimahi Regional Police Station. To analyze these problems, researchers used a qualitative approach with a holistic method. The use of conceptual framework in the form of theory and concepts is used as a knife of analysis by researchers in answering the formulated problems. Theories and concepts used by researchers are Management theory, Routine Activity theory, Sabhara concept, Patrol concept, Two Wheel Patrol concept. The findings during this research are (1) In the implementation of the two-wheeled patrol route the patrol route was determined based on the results of the monthly Cevahi police station anev meeting which was attended by the main officers of the Cimahi police station by looking at which areas there were many cases of theft by ballast. (2) Factors that influence two-wheeled patrols in preventing theft by weighting are still commonly found starting from within to outside factors so that the implementation of two-wheeled patrols is still less than optimal. (3) Efforts of the Sabhara Unit through two-wheeled patrol activities in preventing criminal acts of theft by weighting in the Cimahi Regional Police area by making efforts starting from planning, organizing, implementing, controlling and emphasizing on patrol routes based on monthly anev.